2015
DOI: 10.1021/jacs.5b09888
|View full text |Cite
|
Sign up to set email alerts
|

gem-Difluoroolefination of Diazo Compounds with TMSCF3 or TMSCF2Br: Transition-Metal-Free Cross-Coupling of Two Carbene Precursors

Abstract: A new olefination protocol for transition-metal-free cross-coupling of two carbene fragments arising from two different sources, namely, a nonfluorinated carbene fragment resulting from a diazo compound and a difluorocarbene fragment derived from Ruppert-Prakash reagent (TMSCF3) or TMSCF2Br, has been developed. This gem-difluoroolefination proceeds through the direct nucleophilic addition of diazo compounds to difluorocarbene followed by elimination of N2. Compared to previously reported Cu-catalyzed gem-diflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(68 citation statements)
references
References 76 publications
1
60
0
Order By: Relevance
“…Difluoroalkenes are ar eadily accessible class of substrates. [13] While avariety of methods exist for their synthesis, perhaps the most notable is through aJ ulia-Kocienski olefination protocol utilizing commercially available difluoromethyl 2-pyridyl sulfone (Husr eagent) and aldehydes or ketones,which we found to be useful for our purposes.…”
mentioning
confidence: 99%
“…Difluoroalkenes are ar eadily accessible class of substrates. [13] While avariety of methods exist for their synthesis, perhaps the most notable is through aJ ulia-Kocienski olefination protocol utilizing commercially available difluoromethyl 2-pyridyl sulfone (Husr eagent) and aldehydes or ketones,which we found to be useful for our purposes.…”
mentioning
confidence: 99%
“…Similarly, in other work on the gem ‐difluoroolefination of diazo compounds, Hu et al. reported that gem ‐difluoroolefination of diazo compounds 144 could be achieved by the transition‐metal‐free cross‐coupling of two carbene precursors, namely, diazo compounds and Ruppert‐Prakash reagent, TMSCF 3 ( 147 ) or TMSCF 2 Br ( 145 ) …”
Section: Dihaloolefination Of Diazo Compoundsmentioning
confidence: 81%
“…[14] Later, Hu and coworkers again reported a transition-metalfree difluoroolefination protocol for the cross-coupling of diazo compounds (33 and 36) with TMSCF 3 or TMSCF 2 Br (Scheme 5). [15] The use of sodium iodide (NaI), a less basic activator, instead of a fluoride source led to a relatively slower release of difluorocarbene from TMSCF 3 , which was beneficial for the olefination. The reaction proceeded through a direct nucleophilic addition of diazo compounds to difluorocarbene followed by elimination of N 2 , and furnished a variety of 1,1difluoroalkenes (34 and 37), e. g., difluoroacrylates, diaryldifluoroolefins, and arylalkyldifluoroolefins, which showed a broader 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 substrate scope than that of the Cu-catalyzed difluoroolefination.…”
Section: Gem-difluoroolefination and The Related Transformationmentioning
confidence: 99%
“…Two possible reaction pathways might be involved in this difluoroolefination (Scheme 5), and the direct carbene-carbene cross-coupling is probably less rational (path b) according to the control experiments. [15] Almost at the same time, Wang and coworkers independently disclosed a similar transition-metal-free difluoromethylenation of diaryl diazomethanes and α-diazo esters using TMSCF 2 Br as a difluoromethylene source and tetrabutylammonium bromide (TBAB) as a promoter. [16] The reaction was run under mild conditions and tolerated various functional groups, wherein hydrazones (45) were also readily converted to afford the corresponding 1,1-difluoroolefins (46) in moderate to excellent yields (Scheme 6).…”
Section: Gem-difluoroolefination and The Related Transformationmentioning
confidence: 99%